La antinomia entre el artículo 259° inc. 3 y 4 y el artículo 261° inciso 1.B del código procesal penal, respecto a la detención del agente que ha logrado evitar su detención - Borjas Bonifacio, Karina Analí (2017)
The way to fight the impunity of crimes as a goal of Criminal Procedure Law, will always be latent in our legal system, always seeking the correct administration of justice under the parameters, due process, safeguarded by all the guarantees and principles that In it converges. For this reason, the analysis of "THE ANTINOMY BETWEEN ARTICLE 259 INC.3 and 4 AND ARTICLE 261, INC. 1.B OF THE CRIMINAL PROCEDURE CODE, WITH RESPECT TO THE DETENTION OF THE AGENT WHO HAS ACHIEVED TO PREVENT HIS DETENTION", tries to determine If there is a contradiction between the two rules that prevents their simultaneous application. The present paper proposes to develop both articles, knowing the criteria of interpretation developed by the Constitutional Court to establish if they comply with the requirement of the constitutional principle of judicial reserve. Also with the purpose of providing a proposal for modification of the standard if necessary. It should be added that legal instruments were used as current laws, Plenary Agreements; Doctrine and Jurisprudence in order to discern a correct application of this procedural norm. And in order to verify what was analyzed in this investigation, statistics were collected on the police and preliminary detentions of the Trujillo-La Libertad Jurisdictional District. , Obtaining relevant data for our investig